Strategi Pelayanan Lembaga Penyiaran Publik (LPP) Radio Republik Indonesia (RRI) Denpasar - A. A. A. Ngurah Sumitha Ghanjali (Universitas Warmadewa, 2023)
Public services in Indonesia in the form of services can be done through the media. Public Broadcasting Institution (LPP) Radio Republik Indonesia (RRI) Denpasar is one of the public media agencies that provides services in the form of information. However, as time goes by, many media platforms have emerged that have attracted public attention and the added bureaucratic hierarchy has meant that LPP RRI Denpasar has not been optimal in providing its services. The target of this research is to find out the LPP RRI Denpasar Service Strategy to account for its existence as public media. The formulation of the research problem is: 1) What are the factors causing the LPP RRI Denpasar to not be optimal? 2) What is the service strategy for LPP RRI Denpasar? This research aims to analyze and evaluate the existence of LPP RRI Denpasar as a public media agency whose task is to serve public needs. This type of research is descriptive qualitative with the application of Strategic Management theory according to Fred. R. David. Data collection was carried out using observation, interviews and documentation techniques. The selection of informants used purposive sampling. The research results show that the services of the Public Broadcasting Institution (LPP) Radio Republik Indonesia (RRI) Denpasar are not optimal. In carrying out public services, it is a top-down bureaucracy that is still hierarchical, RRI's image still seems stiff and formal in society, and the diversity of public needs cannot be met considering the decreasing availability of human resources. The strategy carried out by LPP RRI Denpasar is to present its broadcast programs on every media platform that is loved by the public, innovating into multi-platform based media.